Clinical efficacy, safety and tolerability of BIO-C® (micronizedSilymarin) as a galactagogue - Di Pierro, F.; Callegari, A.; Carotenuto, D.; Tapia, M. M. (Acta Biomedica Atenei Parmensis, 2008)
Background and aim of the work: The authors have previously reported the use of Silymarin (a Silybum marianum standardized extract) as a promoter of milk production in cows. Due to the important psychological impact of hypogalactia in women after delivery, we evaluated the role of Silymarin as a safe and effective galactogogue for human species. Methods: 50 healthy women during lactation were enrolled in order to verify the galactogogue role played by an oral treatment with micronized Silymarin (420 mg/day) in comparison with an undistinguishable placebo product. Results: Women orally treated for 63 days with Silymarin showed a clear galactagogue role for the product with an increase of 85.94% of the daily milk production (placebo: +32.09%). No drop out, nor unwanted effects were reported in both groups. Compliance and tolerability were also very good. Conclusions: Silymarin may be considered as a safe and effective herbal product that can be orally administered in order to improve the daily milk production in healthy women after delivery, without affecting milk quality.